Faktor-Faktor Yang Mempengaruhi Non Performing Financing Bank Umum Syariah Di Indonesia - Munawaroh Munawaroh; Murni Dahlena Nst; Dewi Andriyani (Jurnal Riset Akuntansi dan Bisnis, 2021)
This research aims to determine the effect of the type of financing, inflation and the Bi rate on Non-Performing Financing in Islamic commercial banks in Indonesia. In this study used a Quantitative approach. The population in this study is all sharia public banks in Indonesia. The eligible samples in the study were 14 companies. The results of this study show that partially this type of financing has a significant negative effect on non-performing financing at Sharia Commercial Bank in Indonesia while inflation and Bi rate negatively affect non performing financing at Sharia Commercial Bank in Indonesia. Simultaneously the type of inflation financing and Bi rate has a significant effect on non performing financing at Sharia Commercial Bank in Indonesia which is 31.4% while the remaining 68.6% is explained by other variables outside this study.